Corporate social responsibility towards AIDS orphans in South Africa : trends in the motor manufacturing sector and guidelines for corporate action - Neethling, Marcha (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.